The Relationship Between the Availability of Facilities and River Littering Behavior Among the Community of Purwosari II Village, Tamban Subdistrict, Barito Kuala Regency - Aprianti, Rita; Yuseran, Yuseran; Sudjatmiko Setyobudihono; Halimah, Halimah (Sean Institute, 2025)
Waste remains an ongoing environmental issue that must be addressed. The community's lack of concern regarding waste contributes to environmental pollution. This study aims to determine the relationship between the availability of waste disposal facilities and river littering behavior among the residents of Purwosari II Village, Tamban Subdistrict, Barito Kuala Regency. This research uses a quantitative method with an analytic survey type and a cross-sectional approach. Data were collected using a questionnaire regarding the availability of household waste disposal facilities and waste disposal behavior, involving 83 housewives in Purwosari II Village. The data were analyzed using univariate and bivariate methods with the Chi square test. The results showed that the majority of respondents (55) did not have access to waste disposal facilities, while 28 respondents did have access. Additionally, 48 respondents demonstrated poor waste disposal behavior, whereas 35 showed good behavior. The study found a significant relationship between the availability of waste disposal facilities and river littering behavior, with a p-value of 0.000 (<0.05).